Comparative Proteomics of Methicillin-Resistant Staphylococcus aureus Subjected to Synergistic Effects of the Lantibiotic Nisin and Oxacillin - Bergamo Alves, Fernanda Cristina [UNESP]; Albano, Mariana [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Chechi, Jessica Luana [UNESP]; Marques Pereira, Ana Flavia [UNESP]; Furlanetto, Alessandra [UNESP]; Mores Rall, Vera Lucia [UNESP]; Henrique Fernandes, Ana Angelica [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Barbosa, Lidiane Nunes; Fernandes Junior, Ary [UNESP] (Mary Ann Liebert, Inc, 2019)
We investigated the responses and mechanisms of action of methicillin-resistant Staphylococcus aureus (MRSA) metabolism when exposed under sublethal concentrations of the synergistic antibacterial combination of nisin + oxacillin (1/4 of maximum sublethal concentration) and sublethal concentrations of oxacillin only and nisin only. A total of 135 proteins were identified, showing an alteration in the expression of 85 proteins when treatment was compared with untreated bacteria (control). When the bacteria were treated using the combination, there was an increase in the expression of proteins related to resistance (e.g., beta-lactamase) and also in the ones involved in protein synthesis, and there was a decrease in the expression of proteins related to stress and alterations in proteins related to bacterial energy metabolism. Bacterial oxidative stress showed that the combination was able to induce oxidative stress (p < 0.05) and increase enzyme activities and lipid hydroperoxide levels compared with individual treatments. The analysis of cell ultrastructure showed damage in MRSA, especially on the bacterial wall and the plasma membrane, with cell lysis and death. Thus, the changes caused by these treatments affected different proteins related to the bacterial biological processes and signaling pathways such as cell division, structure, stress, regulation, bacterial resistance, protein synthesis, gene expression, energetic metabolism, and virulence. It was observed that synergism among antimicrobials has high potential in therapeutic use and may reduce the required amounts of antibacterial substances in addition to being effective on different targets in bacterial cells.
Keywords: antimicrobial peptide; bacterial resistance; synergism; LC-MS/MS; oxidative stress; transmission electron microscopy